Day 2 Tue, November 13, 2018 2018
DOI: 10.2118/193189-ms
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Casing Fatigue Failure During Multistage Fracturing Operations

Abstract: Tubular fatigue failures have been commonly reported in geothermal and heavy oil wells with cyclic steam injection operations. Recently, possible fatigue failures in casing connections during multistage fracturing operations have also been reported in the literature. These occurrences raised the question of whether casing fatigue is a real problem, even for shale plays. This paper describes fatigue modeling and analysis of the casing connections during fracturing operations to provide additional information ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…The industry tendency to go to slim-hole DwC, with ever increasing operating loads is not a foreseeable future. Also, according to Liu et al (2018) recent literature have reported casing fatigue during multistage hydraulic fracturing particularly at casing joints. The study attributed cause of casing fatigue loading to cyclic hydraulic fracturing with varying temperature between stages.…”
Section: Fatigue Failurementioning
confidence: 99%
See 1 more Smart Citation
“…The industry tendency to go to slim-hole DwC, with ever increasing operating loads is not a foreseeable future. Also, according to Liu et al (2018) recent literature have reported casing fatigue during multistage hydraulic fracturing particularly at casing joints. The study attributed cause of casing fatigue loading to cyclic hydraulic fracturing with varying temperature between stages.…”
Section: Fatigue Failurementioning
confidence: 99%
“…It also indicate formation slippage as the main reason for casing failure during waterflooding. Simulation Liu et al, 2018;Xi et al, 2018;Zhao et al, 2018;Zhang et al, 2016 Vertical /Drilling, completion and production Collapse pressure from salt rock creep, annulus pressure build-up owing to fluid thermal expansion in sealed annuli.…”
mentioning
confidence: 99%
“…The casing under cycling loads are available to generate residual strain, and the accumulation of induced stresses from hydraulic fractures increases the maximum principal stress near the wellbore. [11][12][13] Moreover, in acidizing fracturing conditions, activation and slip of faults caused by fluid entering the formation can also seriously affect casing integrity. [14][15][16][17][18][19][20][21][22][23] At present, numerical simulation analysis is the main method of casing deformation and failure mechanism research.…”
Section: Introductionmentioning
confidence: 99%
“…Another reason for casing deformation was proposed by Hagshenas et al (2017) and Liu et al (2017) who noted that additional load is exerted on the casing by fracture slip through the wellbore. Liu et al (2018) pointed out that local stresses and shear of weak formation are the main causes of casing deformation during fracturing. These local stresses are typically tangential, axial and radial resulting from in situ stresses.…”
Section: Introductionmentioning
confidence: 99%